The role of chemosensory protein 10 in the detection of behaviorally active compounds in brown planthopper, Nilaparvata lugens. (31st January 2019) - Waris, Muhammad Irfan; Younas, Aneela; Adeel, Muhammad Muzammal; Duan, Shuang‐Gang; Quershi, Sundas Rana; Kaleem Ullah, Rana Muhammad; Wang, Man‐Qun
Abstract: Chemosensory proteins (CSPs) play important roles in insects' chemoreception, although their specific functional roles have not been fully elucidated. In this study, we conducted the developmental expression patterns and competitive binding assay as well as knock‐down assay by RNA interference both in vitro and in vivo to reveal the function of NlugCSP10 from the brown planthopper (BPH), Nilaparvata lugens (Stål), a major pest in rice plants. The results showed that NlugCSP10 messenger RNA was significantly higher in males than in females and correlated to gender, development and wing forms. The fluorescence binding assays revealed that NlugCSP10 exhibited the highest binding affinity with cis ‐3‐hexenyl acetate, eicosane, and (+)‐β‐pinene. Behavioral assay revealed that eicosane displayed attractant activity, while cis ‐3‐hexenyl acetate, similar to (+)‐ β ‐pinene significantly repelled N. lugens adults. Silencing of NlugCSP10, which is responsible for cis ‐3‐hexenyl acetate binding, significantly disrupted cis ‐3‐hexenyl acetate communication. Overall, findings of the present study showed that NlugCSP10 could selectively interrelate with numerous volatiles emitted from host plants and these ligands could be designated to develop slow‐release mediators that attract/repel N. lugens and subsequently improve the exploration of plans to control this insect pest.